Sensory system design for perturbation-based balance rehabilitation - Lee, Jessica He Bing (2014)
This project aims to design and implement a sensory system to improve on the current rehabilitation machine which is capable of detecting the ground reaction force when it is worn by the patient. The ground reaction force would then be used to determine the type of gait phase the patient is in, and hence allowing the therapist to induce the perturbations on the rehabilitation machine at different stages. This is so, that the simulated perturbations can be executed at random pattern in order to make unpredictable for the patient.